THE ROLE OF THE FAMILY IN CHILDREN’S COGNITIVE DEVELOPMENT: - - Krulj, Jelena; Marković, Emilija; Lazović, Nataša (Metodička teorija i praksa, 2026)
In this paper has been given reconsideration of the role of the family in children’s cognitive development with the focus on different factors which give the frame to this process. There have been given reconsideration of theoretical frames which are explaining how the economic status of the family, parent’s involvement, th quality of the relation parent-child and socio-emotional support influence the children’s cognitive development. Based on the Theory of Economic Investments there have been given reconsideration of how parents use the recourse like time, education and activities in the free time for improving of cognitive abilities of their children. Research have shown that children from the families with higher economic status and higher parent’s educational level reach better cognitive results, but also that the stress caused by economic problems can have negative influence on children’s development. The Attachment Theory stresses the importance of emotional stability an security in early life phases for development of cognitive functions. Also, the importance of positive parenting which is characterized by warmth, support and non violent methods of discipline has the huge influence on the development of intellectual and social abilities of children. It is concluded that family environment, like the activities that parents are performing with their children play the main role in forming of stimulative environment for cognitive development, so the continuous support and parent’s involvement are from the essential importance for children’s early development.